Laksana pratimānawitthayā kh̨̄ong hun r̄ưang Rāmmakīan kh̨̄ong Krom Phrarātchawang B̨̄ow̨̄onwichaichān - Wanthanī Mūangbun (Sathāban Nātduriyāngkhasin, Krom Sinlapāk̨̄on, 1996)
Study on Thai puppetry and presentation based on text of Rāmmakīan, version of Ramayana by Phutthaȳ̨otfā Čhulālōk, King of Siam, 1737-1809.